2020
DOI: 10.3346/jkms.2020.35.e239
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent Plasma Therapy in Coronavirus Disease 2019: a Case Report and Suggestions to Overcome Obstacles

Abstract: Coronavirus disease 2019 (COVID-19) is rapidly spreading around the world, causing much morbidity and mortality everywhere. However, effective treatments or vaccines are still not available. Although convalescent plasma (CP) therapy can be useful in the treatment of COVID-19, it has not been widely used in Korea because of the concerns about adverse effects and the difficulty in matching patients to donors. The use of ABO-incompatible plasma is not contraindicated in treatment, but can be hesitated due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
0
22
0
1
Order By: Relevance
“…El plasma convaleciente disminuyó la carga viral y no se informaron efectos secundarios mayores (20,21) . Un reporte de caso (23) se señaló que dos pacientes que desarrollaron dificultad respiratoria cuatro días después de que la terapia con plasma convaleciente mostró una mejoría clínica.…”
Section: Discussionunclassified
“…El plasma convaleciente disminuyó la carga viral y no se informaron efectos secundarios mayores (20,21) . Un reporte de caso (23) se señaló que dos pacientes que desarrollaron dificultad respiratoria cuatro días después de que la terapia con plasma convaleciente mostró una mejoría clínica.…”
Section: Discussionunclassified
“…A summary of the primary literature describing the use of convalescent plasma is found in Table 2 [ 15 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ]. Sixteen reports of convalescent plasma in COVID-19 ( n = 5353 treated), four in MERS-CoV ( n = 13 treated), and five in SARS-CoV ( n = 125 treated) were identified.…”
Section: Reports Of Efficacy and Safety Of Convalescent Plasma For Trmentioning
confidence: 99%
“…There were two randomized control trials [ 20 , 21 ], and there was a comparator group in seven COVID-19 studies, and in two SARS-CoV studies. Most of the identified studies reported a benefit of convalescent plasma therapy, manifested as clinical improvement, reduced mortality, longer survival time, earlier discharge, increased viral clearance or increased virus-specific IgG or IgM following treatment [ 15 , 20 , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ]. Before COVID-19, the two largest studies were reported, retrospectively, from the same group in Hong Kong during the SARS-CoV outbreak of 2003 [ 24 , 25 ].…”
Section: Reports Of Efficacy and Safety Of Convalescent Plasma For Trmentioning
confidence: 99%
See 2 more Smart Citations